Dexmedetomidine versus Propofol Sedation Reduces Delirium after Cardiac Surgery; A Cross Sectional Study - Ahmad, Nouman; Naseem, Chanda; Naeem, Faisal; Shahid, Omama; Tauqeer Ali Shah; Ahmad Tariq, Sheikh Muhammad; Saleem, Amna (Indus Journal of Bioscience Research, 2025)
Introduction: Postoperative delirium (POD) represents a notable complication subsequent to heart surgery. The use of dexmedetomidine for delirium prophylaxis is still debated. The authors hypothesised that dexmedetomidine sedation after cardiac surgery would reduce the incidence of postoperative delirium (POD). Materials and Methods: This study included heart surgery patients aged ≥60, excluding those with dementia, delirium, or major depression. ICU patients received four hours of propofol or dexmedetomidine (initial dose 0.4 μg/kg, then 0.2–0.7 μg/kg/h infusion). Delirium was assessed every 12 hours for five days, with POD frequency as the primary outcome. Results: This study compared dexmedetomidine and propofol for sedation in cardiac surgery patients. The dexmedetomidine group had a shorter ICU stay (2.2 ± 0.9 vs. 3.5 ± 1.3 days, p = 0.01), earlier recovery (18.4 ± 4.5 vs. 22.7 ± 5.2 hours, p = 0.02), and lower delirium incidence (16% vs. 30%, p = 0.08). Hospital stays were shorter (2.4 ± 0.9 vs. 3.8 ± 1.2 days, p < 0.001), pain scores were lower (3.2 ± 1.1 vs. 5.6 ± 1.3, p < 0.001), and fewer required rescue analgesia (20% vs. 44%). Despite higher sedative costs, dexmedetomidine proved superior in delirium control and recovery outcomes. Conclusion: Overall, compared to propofol-based sedation, postoperative dexmedetomidine sedation had fewer cases of postoperative delirium (POD), a later start, and a shorter duration in older patients undergoing heart surgery.